A Navigational Compass for Veterinary Professionalism: Integrating Stakeholder Perspectives to Guide Veterinary Care and Career Success - Gordon S; Janicke H; Bradberry K; Weston J; Bolwell C; Benschop J; Parkinson T; Gardner D (MDPI (Basel, Switzerland), 2026)
Professionalism is central to veterinary practice, shaping not only the quality of care provided to animals but also the wellbeing of practitioners, the satisfaction of clients, and the sustainability of the profession. Prior research has catalogued various attributes of professionalism that are important for career success, but few studies have integrated these multiple perspectives into a cohesive framework. This study synthesizes insights from three key veterinary stakeholder groups—students, clinical practitioners, and clients—using a multi-methods approach including surveys, focus groups, critical incident interviews, and client complaint analyses. Across the datasets, ranking of Likert-scale responses and thematic analysis revealed four recurring themes that were identified as essential for career success: ‘Effective communication’; ‘Accountability, integrity, trustworthiness, and honesty’; ‘Personal wellbeing’; and ‘Quality of service’. These themes were organized into a unifying theoretical model of veterinary professionalism, conceptualized as a ‘navigational compass’, comprising three domains of care: patient-centered care, relationship-centered care, and self-care. By conceptualizing professionalism in terms of a compass, the model illustrates how veterinarians can draw on key professionalism attributes, coupled with consideration of the three domains of veterinary care, to navigate the challenges of practice and sustain long-term career success. The compass provides a reflective framework to guide veterinarians and educators, to support the integration of professionalism into curricula and to guide careers toward excellence in care and lasting personal fulfilment.
Keywords: professionalism; veterinary students; veterinary clinical practitioners; veterinary clients; communication; accountability; integrity; trustworthiness; honesty; wellbeing; service; patient-centered care; relationship-centered care; self-care